A SYSTEMIC ANALYSIS OF HIGH SCHOOL TEACHERS' ARGUMENTATIVE WRITING :A Case Study in Bandar Lampung - Akmal, Refdi (2012)
This thesis is to report on teachers' ability in composing expository texts. The texts were composed by six high school teachers in Bandar Lampung, Lampung, Indonesia. This study is a descriptive qualitative case study investigating three Analytical and three Hortatory Expository texts. Those texts were analyzed using Systemic Functional Linguistics (SFL) to deal with the textual, experiential and interpersonal metafunctions which were exposed within the texts' Theme, Transitivity and Mood systems. The results of texts analyses then were confirmed and validated through interviews conducted with the teachers. The result of this study shows that the teachers could demonstrate appropriate strategies to compose the texts although some problems of writing were evident in the texts. The grammatical analyses indicate that the writers had successfully attempted to use some of the main conventions of written argumentative discourse. In this case, to construe textual metafunction, the teachers could employ the demands of the generic form of arguing genre, the linguistic devices as well as the thematic progression. Furthermore, referring to experiential metafunction, the teachers could demonstrate their ability to use various linguistic resources such as appropriate conjunction system and appropriate Process types, Circumstantials and Nominalisations. Finally, interpersonally, the writers could enrich the text with the use of appropriate Modality to create objective arguments and communicate with the readers. However, the study reveals that not all of the teachers' texts can be considered successful or mature texts in that they seem to have problems with Argument development characterized with lack of fact and objective evidence, inconsistency of argument, and absence of intertextuality. Besides, the inappropriate use of imperative mood, realis/universal statements and some syntax errors are also found. It is found that the teachers' problems were mainly to do with their time management to carry out the task which resulted in their inability to give maximum efforts to work with the texts. In addition their background knowledge and language competence as well as their commitment to carry out the task also appeared to be problems in producing the texts. Thus, the teachers are suggested to commit to more practices and to have effective teacher trainings to maintain and improve the teachers' professional competence particularly to concern the issue of SFL and GBA within the curriculum.